Cause-of-death analysis in patients with cardiac resynchronization therapy with or without a defibrillator: a systematic review and proportional meta-analysis. Issue 3 (28th June 2017) - Barra, Sérgio; Providência, Rui; Duehmke, Rudolf; Boveda, Serge; Begley, David; Grace, Andrew; Narayanan, Kumar; Tang, Anthony; Marijon, Eloi; Agarwal, Sharad
Abstract: Aims: The additional benefit of a defibrillator in cardiac resynchronization therapy (CRT) patients is a matter of debate. Cause-of-death analysis in a CRT population has been recently proposed as a useful approach to gain insight into this problem. We performed a systematic review and meta-analysis looking at cause of death in studies involving CRT subjects with (CRT-D) or without (CRT-P) a defibrillator. Methods and results: Literature search performed from inception to 31 March 2016 for relevant studies. Proportional and conventional meta-analyses were performed to obtain and compare causes of death in CRT-D vs. CRT-P patients, including sudden cardiac death (SCD), all-cause mortality, heart failure, cardiovascular, and non-cardiovascular mortalities. The systematic review included a total of 44 studies and 18 874 patients (13 248 receiving CRT-D and 5626 receiving CRT-P), representing 48 504 patient-years of follow-up. CRT-D recipients were younger, more often male, had lower NYHA class, less atrial fibrillation, more ischaemic heart disease and were more often on beta-blockers than those receiving CRT-P. There were an additional 42 deaths per 1000 patient-years in the CRT-P group compared with CRT-D (97 ± 9, 95% CI 79–115 vs. 55 ± 5, 95% CI 44–65, respectively), of which 35.7% were due to SCD (20 ± 2, 95% CI 15–24 vs. 5 ± 1, 95% CI 3–6) and the remaining 64.3% due to non-SCD. Of all deaths reported in CRT-D and CRT-P patients, 9.1% and 20.6% were due to SCD, respectively. The extent of SCD in CRT-P patients significantly increased in studies with higher percentage of males, ischaemic cardiomyopathy and NYHA class 3. Conclusion: Overall, compared with CRT-D patients, unadjusted mortality rate was almost two-fold higher in CRT-P recipients, with SCD representing one third of the excess mortality. Rate of SCD was significantly higher in certain subgroups (males, ischaemic cardiomyopathy, NYHA class 3), where a CRT-D may be of more pronounced benefit. This deserves further focused investigation.